2010
DOI: 10.1103/physrevb.82.020510
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inhomogeneities in iron pnictide superconductors: The formation of charge stripes

Abstract: The heterogeneous coexistence of antiferromagnetism (SDW) and superconductivity on a mesoscopic scale was observed in iron-pnictides in many recent experiments. We suggest and discuss the scenario in which the heterogeneity is caused by formation of domain walls inherent to the SDW state of pnictides at a proper doping or under applied pressure. Superconductivity would emerge from the modulated SDW structure. The phenomenon is akin to the FFLO-phase in superconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 29 publications
3
40
1
Order By: Relevance
“…[46][47][48] However, for the concentration studied here, high-resolution resonance magnetic x-ray diffraction reported no signs of incommensurability. 49 Neutron scattering studies have reported incommensurate order appears only at higher doping levels (x > 0.056).…”
Section: 40contrasting
confidence: 50%
“…[46][47][48] However, for the concentration studied here, high-resolution resonance magnetic x-ray diffraction reported no signs of incommensurability. 49 Neutron scattering studies have reported incommensurate order appears only at higher doping levels (x > 0.056).…”
Section: 40contrasting
confidence: 50%
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent discovery (12) that better superconductivity appears with "optimal inhomogeneity" (26) of oxygen defect (Oi) ordering opens the question of the nature of the remaining disordered medium, the topic of the present paper. The separation into an ordered network and a strained embedding medium provides a basis for the two electronic components (27)(28)(29) which have been proposed as the key feature for certain theories of high temperature superconductivity (30)(31)(32).…”
mentioning
confidence: 99%
“…Several theoretical investigations have focused on charge and spin states in the vicinity of the crossover regime. [10][11][12] The coexistence of the order parameters of the incommensurate spin-densitywave and superconducting (IC-SDW + SC) states has been investigated in the crossover regime for s +− -or s ++ -wave symmetry. [10][11][12] The homogeneous coexistence of the AF and SC states has been suggested for Ba(Fe 1−x Co x ) 2 As 2 on a microscopic level, [13][14][15] whereas microscopic or mesoscopic segregation of the AF and SC phases has been suggested for K-doped Ba(Fe 1−x Co x ) 2 As 2 .…”
mentioning
confidence: 99%
“…[10][11][12] The coexistence of the order parameters of the incommensurate spin-densitywave and superconducting (IC-SDW + SC) states has been investigated in the crossover regime for s +− -or s ++ -wave symmetry. [10][11][12] The homogeneous coexistence of the AF and SC states has been suggested for Ba(Fe 1−x Co x ) 2 As 2 on a microscopic level, [13][14][15] whereas microscopic or mesoscopic segregation of the AF and SC phases has been suggested for K-doped Ba(Fe 1−x Co x ) 2 As 2 . [16][17][18] The topics have been investigated mainly for the Ba 122 series 19 and it is presently unclear whether the observed phenomena are inherent to all iron-based superconductors with a crossover regime.…”
mentioning
confidence: 99%